2011
DOI: 10.1007/s00253-011-3622-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution of Saccharomyces cerevisiae to generate strains with enhanced glycerol production

Abstract: Adaptive evolution of microorganisms has largely been used to study evolutionary responses to various environmental factors, as well as to create new strains for industrial applications. Although new industrial strains can be constructed using recombinant DNA technologies, consumer concerns about genetically modified (GM) organisms limit their use, particularly in food and beverage production. We have applied adaptive evolution with sulfite at alkaline pH as a selective agent to generate a stable mutant of Sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 39 publications
0
51
0
1
Order By: Relevance
“…For both strains, the diversion was explained by marked increased synthesis of glycerol and 2,3-butanediol, which were both used as carbon and redox sinks. Thus, compared to previous attempts to divert carbons toward the pentose phosphate pathway (26) or toward glycerol by adaptive evolution using sulfites (25), this evolutionary strategy resulted in a much higher diversion of carbons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For both strains, the diversion was explained by marked increased synthesis of glycerol and 2,3-butanediol, which were both used as carbon and redox sinks. Thus, compared to previous attempts to divert carbons toward the pentose phosphate pathway (26) or toward glycerol by adaptive evolution using sulfites (25), this evolutionary strategy resulted in a much higher diversion of carbons.…”
Section: Discussionmentioning
confidence: 99%
“…This property has been exploited in recent years by conducting adaptive laboratory evolution (ALE) experiments to study the principles and characteristics of evolution (18,19,20). Adaptive evolution, based on long-term adaptation of yeast under environmental or metabolic constraints, has been used to improve yeast strains for biotechnological applications, including wine making (21,22,23,24,25,26).…”
mentioning
confidence: 99%
“…Sulphite tolerance tests revealed that seven of the candidate progenies could not grow in a medium containing sulphite. Since sulphite tolerance is dominant (Kutyna et al, 2012), these colonies were not likely to be hybrids (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…To date, using genetic engineering [20,43,44] and non-GM techniques, [45] such as classical breeding (hybridization), adaptive laboratory evolution, and mutagenesis, several non-GM and GM wine strains have been developed with increased robustness, fermentation performance, health-related properties, and/or sensory attributes. Examples include strains that produce wines with lower alcohol levels; [46][47][48][49][50][51][52][53][54][55] mutants that limit the production of unwanted hydrogen-sulfide off-flavors and volatile acidy; [56][57][58] and strains that produce desirable esters, [59,60] terpenes, [61] and thiols ( Figure 18). [62][63][64][65][66][67][68][69][70] Efforts are also underway to express the a-guaiene-2-oxidase from grapevine in S. cerevisiae, thereby equipping wine yeast to transform grapederived a-guaiene to the sought-after spicy aroma compound of Shiraz wine, rotundone.…”
Section: Bioengineered Yeast Put Synthetic Dna To Work In Industrymentioning
confidence: 99%